Dietary long-chain, but not medium-chain, triglycerides impair exercise performance and uncouple cardiac mitochondria in rats. - Murray, A; Knight, N; Little, SE; Cochlin, L; Clements, M; Clarke, K (2011)
Short-term consumption of a high-fat diet impairs exercise capacity in both rats and humans, and increases expression of the mitochondrial uncoupling protein, UCP3, in rodent cardiac and skeletal muscle via activation of the transcription factor, peroxisome proliferator-activated receptor α (PPARα). Unlike long-chain fatty acids however, medium-chain fatty acids do not activate PPARα and do not increase muscle UCP3 expression. We therefore investigated exercise performance and cardiac mitochondrial function in rats fed a chow diet (7.5% kcal from fat), a long-chain triglyceride (LCT) rich diet (46% kcal from LCTs) or a medium-chain triglyceride (MCT) rich diet (46% kcal from MCTs). Rats fed the LCT-rich diet for 15 days ran 55% less far than they did at baseline, whereas rats fed the chow or MCT-rich diets neither improved nor worsened in their exercise capacities. Moreover, consumption of an LCT-rich diet increased cardiac UCP3 expression by 35% and decreased oxidative phosphorylation efficiency, whereas consumption of the MCT-rich diet altered neither UCP3 expression nor oxidative phosphorylation efficiency. Our results suggest that the negative effects of short-term high-fat feeding on exercise performance are predominantly mediated by long-chain rather than medium-chain fatty acids, possibly via PPARα-dependent upregulation of UCP3.